Design Of Automatic Lighting Instructions Based On Pir Gen 3 Sensors for Physics Learning in The Electronics Skills Course - Saputro, Handoyo; Winingsih, Puji Hariati; Saputri, Ratna; Erlangga, Sony Yunior; Bullingga, Nils; Bergman, Luc; Bergman, Patrick (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2024)
This research produces an automatic light physics demonstration tool based on a PIR sensor in the Electronics Skills course. This type of research is development research which refers to the 4-D model according to Thiagarajan with 4 stages including the definition, design, development and dissemination stages. This research was tested in the Physics Education Study Program. Data collection techniques in this research include observation, interviews, and questionnaires. The data analysis technique used is descriptive statistical analysis. The results of this research obtained several findings including: (1). The product is a PIR sensor-based automatic light electrical circuit demonstration tool; (2). The feasibility test of teaching aids with an average rating of 33.33% Agree (S) and 66.67% Strongly Agree (SS), and the feasibility test of teaching aids with an average rating of 51.85% Agree (S) and 48.15% Strongly Agree (SS). Test the readability of students' responses to teaching aids and teaching aid guides with an average rating of 3% Disagree (TS), 43% Agree (S) and 54% Strongly Agree (SS). Based on the test results, it can be concluded that the PIR sensor-based automatic light electrical circuit teaching aids and guides are suitable for use in physics learning